SOCIAL OUTCOMES OF THE DEVELOPMENT OF THE HIGHER EDUCATION SYSTEM AND YOUTH POLICY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article discusses the organization of education in the modern era, especially the higher education system, the increasing attention given to youth, and the new requirements being placed on education today. In this regard, the higher education system must respond as effectively as possible to the demands arising from the uncertain processes of globalization and the rapid technological and information development of society. The prospects of implementing state policy in the field of higher education institutions are explained through their specific outcomes.